THE ACQUISITION OF VOCABULARY BY THE YOUNG LEARNERS THROUGH CHILDREN SONGS - Yuni Andari, Ida Ayu Made; Ngurah Parthama, I Gusti; Winaya, I Made (Udayana Journal of Social Sciences and Humanities, 2024)
This study emphasizes the English learning process for young learners in acquiring English vocabulary through children's songs. The aims of this study are to find out what kinds of vocabulary that the young learners acquire through children's songs and analyze how to do the internal and external factors that influence the acquisition of vocabulary acquired by young learners through children's songs. The data in this study were taken from observing 4-5 years old young learners. The data were collected directly by observing the young learner and questionnaire. The technique used in obtaining the data from the object was note-taking. It was used to know the progress of the young learner during observation. Then, the collective data were analyzed using the qualitative method. The findings of this study showed that children's songs had a positive influence on acquiring English vocabulary. First, the result of this research shows that there are eight songs that were taught to the children. Hooray School kindergarten students were able to master 62 vocabularies from all of the songs. There are 31 nouns, 20 verbs, 7 adjectives, 2 prepositions, 1 pronoun, and 1 adverb. Second, the internal factor includes age, experience and learning style. The external factors consist of motivation, instruction, and access to foreign speakers. Children who are more experienced, motivated, and have access to native speakers, are easier to acquire English vocabulary.